Акустичні характеристики повітряних струмин при їх витіканні - Возняк, О. Т.; Желих, В. М.; Ольшанська, О. Я. (Видавництво Державного університету “Львівська політехніка”, 1999)
In this article there are presented results of investigations of air jet’s acoustic characteristics, that give a possibility to make a control of air supply device choice at air distribution calculation. Dependence of noise level from jet’s leakage velocity and size of air supply device has been investigated.
Keywords: 697.9